MEANS FOR SECURING THE CONTRACT OF SALE THAT DERIVE FROM THE PROCESS OF EU INTEGRATION: IN KOSOVA AND ALBANIA - Belegu, Majlinda (European Scientific Journal, ESJ, 2015)
Contract parties enter into a contract because from the contracted job they expect determined results. However it happens that debtor doesn’t fulfill his obligation, or he fulfills the obligation with the delay whereas the item respectively service is not of the contracted quality. In these and in the similar cases, if the debtor doesn’t fulfill willingly his obligation, to the creditor it remains to negotiate compensate the eventual damage or it remains that he will realize his rights through court. Court procedure usually lasts a lot and causes additional damages whereas even if the judgment is taken a question appears if the request could be realized with the execution procedure. Therefore parties very frequently contract special institutes by which the execution of obligations is ensured by debtor. Means of securing contract are always applied if parties have foreseen this explicitly by contract , whereas this is rarely regulated by the law. Contract could be “perfect”, “strong”, as soon as parties agree with the essential parts of contracts. However, contract parties sometimes apart of the main contract they sign a second hand contract-accessory or they add to the contract special disposalsclause, so the contract to be strong and that through these parties are pushed to precisely fulfill their obligations